Evolutions in microstructure and mechanical properties of laser lap welded AZ31 magnesium alloy via beam oscillation. (September 2019) - Gao, Ming; Wang, Hekang; Hao, Kangda; Mu, Hongyu; Zeng, Xiaoyan
Highlights: Circular beam oscillation was introduced to laser lap welding of Mg alloy. The undercut defect was eliminated with appropriate oscillating parameters. The columnar grains were disappeared with the formation of equiaxed grains. The element distribution was uniform at the lap interface due to beam oscillation. The weld mechanical properties were closely related to the width at lap interface. Abstract: Achieving high performance laser lap weld of the magnesium alloy is one of the most effective methods to realize lightweight of the auto body. In this study, the weld appearance, microstructure and tensile properties of the magnesium alloy were investigated via beam oscillation. It was found that the width at the lap interface increases with the increase of the radius or the decrease of the frequency. Moreover, the beam oscillation can break up the growth of the columnar grains at the weld edge by decreasing the temperature gradient. The broken dendrites are then rolled to the weld center via strong convection and eddy effects, which act as nucleation sites for the equiaxed dendrite. It was confirmed that the general Hall-Petch relation is not suitable for the lap weld of the magnesium alloy. The width at the lap interface rather than the grain size is the main factor affecting the fracture strength, which is beneficial to improve the mechanical properties by reducing the stress concentration. With the width at the lap interface increasing from 2.25 to 5.75 mm, the fracture force increases from 4.18 to 5.50 kN accordingly.